2022
DOI: 10.1155/2022/6309679
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Genetics of Tuber Yield and Resistance to Mite to Avoid Mite Incident and to Increase the Productivity of Cassava (Manihot esculenta Crantz)

Abstract: Mite (Tetranychus urticae) that attacks the cassava plants during dry season can reduce the yield up to 53%, depending on plant age and duration of attacks. The objective of the trial was to evaluate the cassava promising clones for tuber root yield and mite resistance. The field trial was done in Malang, East Java, Indonesia, in 2018 with fifteen clones using a randomized complete block design, with three replications. The glass house experiment for mite evaluation was done in Malang in 2018. A total of fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…[17] reported that tuber yield of 24 clones in 2018 ranged from 22.4 to 51.5 t.ha -1 (average 34.6 t.ha -1 ), and in the 2019 tuber yield ranged from 24.1 t.ha -1 to 54.6 t.ha -1 (average 38.6 t.ha -1 ). While [18] reported that the fresh tuber yield of 15 genotypes in 10 months ranged 30.33-55.67 t.ha -1 with mean 41.34 t.ha -1 . It can be seen that the average tuber yield in this experiment was not significantly different from that of [17], but lower than that reported by [18] because this study has entered the multi-location test stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] reported that tuber yield of 24 clones in 2018 ranged from 22.4 to 51.5 t.ha -1 (average 34.6 t.ha -1 ), and in the 2019 tuber yield ranged from 24.1 t.ha -1 to 54.6 t.ha -1 (average 38.6 t.ha -1 ). While [18] reported that the fresh tuber yield of 15 genotypes in 10 months ranged 30.33-55.67 t.ha -1 with mean 41.34 t.ha -1 . It can be seen that the average tuber yield in this experiment was not significantly different from that of [17], but lower than that reported by [18] because this study has entered the multi-location test stage.…”
Section: Resultsmentioning
confidence: 99%
“…While [18] reported that the fresh tuber yield of 15 genotypes in 10 months ranged 30.33-55.67 t.ha -1 with mean 41.34 t.ha -1 . It can be seen that the average tuber yield in this experiment was not significantly different from that of [17], but lower than that reported by [18] because this study has entered the multi-location test stage. Harvest index had a range between 0.32 to 0.63 with an average of 0.51.…”
Section: Resultsmentioning
confidence: 99%
“…The implication was a good clone on Entisol soil would generally be good in Alfisol soil. However, another experiment showed interaction between genotype and environment for tuber yield [16,17,18,19,20]. The genotype factor was significantly difference for the fresh tuber yield (Table 5).…”
Section: Variance Component and Heritabilitymentioning
confidence: 95%
“…This clone has the potential to be released as a new variety. However, this clone needed to be evaluated in a minimal eight environments before releasing this clone because the fresh tuber yield is affected by interaction between genotype and environment [16,17]. Farmers consider the fresh tuber yield in selecting the variety.…”
Section: Variance Component and Heritabilitymentioning
confidence: 99%
“…For example, in maize yield trials, high‐producing commercial varieties are used for controls when analyzing new hybrids’ abiotic stress tolerance and provide a direct comparison of the performance of possible new varieties compared to what is currently commercially grown (Setimela et al., 2017). The use of checks is a widespread practice in agriculture variety development, including in programs for maize, wheat, sweet potato, soy, and cassava (Gasura et al., 2021; Mondal et al., 2016; Setimela et al., 2017; Sholihin et al., 2022; Webster et al., 2021); however, these checks only provide direct comparisons to adjacent plots, and their relevance diminishes the further a trial plot is located from the check.…”
Section: Introductionmentioning
confidence: 99%